Characteristics of Extract Tamarillo Seeds (Cyphomandra betacea Sendtn) on the treatment of Type of Solvent and Temperature - Budiasih, Ni Nyoman; Wartini, Ni Made; Suparthana, I Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2021)
Tamarillo  seeds have potential as a source of antioxidants. This study aims to determine the effect of the type of solvent and extraction temperature on the characteristics of the tamarillo seed extract, determine the type of solvent and extraction temperature that can produce tamarillo seed extract with the best characteristics. And 3) determine the specific temperature and pH that produces the extract Tamarillo seeds with the highest stability. This study used a randomized block design (RBD) 2 factors with 3 group. The sample extraction process used maceration method. The results showed that the treatment of solvent type and extraction temperature and their interactions affected the yield parameters, pH, total anthocyanin antioxidant capacity. The treatment of ethanol solvent and extraction temperature of 50°C was the best treatment to obtain the extract of Tamarillo seeds with the characteristics of yield, 9.98% yield, pH 3.33, total anthocyanin 27.71 mg/L, antioxidant capacity 1,956.70 mg GAE/100 g.